Examining The Impact of a DSP Project Through a Comparative Adult Education Lens: A Snapshot of Principal Professional Development for Education Internationalization in Beijing, China - Haijun Kang; Lei Lyu; Qi Sun (Educational Considerations, 2016)
Through the lenses of comparative adult education and international educational leadership development, this study explores the learning experiences of local school principals after they participated in a professional development program named "Domestic Study Program" (DSP) in Beijing. A qualitative narrative inquiry was applied and four school principals who self-reported as experiencing personal and professional improvement through the DSP program were interviewed. Their lived learning experiences as adult learners through the DSP project were sorted, categorized, grouped, and regrouped following the qualitative research data analysis protocols suggested by Rossman and Rallis (2003) and Creswell (2014). The research indicates that the four local principals experienced major changes in the areas of self-perception, ways of thinking, and ways of doing. The findings are interpreted through the lenses of comparative adult education and international educational leadership development.
Keywords: Domestic Study Program (DSP); international schools; Literature Review; Conceptual Frameworks; Principals; adult learner; Individual perspective; Integrated perspective; data; research methods; thinking; impact; snapshot; professional development; education; China